Molecular simulations of competitive adsorption behavior between CH4-C2H6 in K-illite clay at supercritical conditions. (15th January 2020) - Zhang, Lu; Liu, Chao; Li, Qibin
Highlights: The adsorption capacity of pure CH4, C2 H6 and CH4 /C2 H6 binary gases in K-illite clay is analyzed. The effects of pressure, temperature, apertures and mole fraction are considered in competitive adsorption of CH4 /C2 H6 . The adsorption selectivity of C2 H6 /CH4 is more than unity. The second adsorption peak of C2 H6 is fade away with the content of CH4 in competitive adsorption. Abstract: Methane (CH4 ) and ethane (C2 H6 ) are dominating compositions in natural gas produced from shale, approximately 80~90 percent. For efficient development and utilization of shale gas, the competitive adsorption behavior between CH4 and C2 H6 is considerable significance to make sure the storage and transportation mechanisms in the pore structure of shale. The adsorption behavior of CH4 -C2 H6 in K-illite slits is studied with wide range of aperture (1.5~5.5 nm), pressure (≤50 MPa) and temperature (320~380 K) by using Grand Canonical Monte Carlo (GCMC) simulations and molecular dynamics (MD) simulations. The adsorption isotherms, isosteric heats, density distribution and absorbed site are used to analyze the pure and binary adsorption behavior considering the effects of temperature, pressure and contents. The results indicate that the pressure has a large influence on the adsorption capacity of C2 H6 and CH4 . At the low pressure, the adsorption capacity of C2 H6 is stronger than that of CH4 . With the increasing pressure, CH4 molecule shows the stronger increasing adsorption behavior than C2 H6 . From the results of adsorption isotherms of pure gas, excess adsorption amounts of pure CH4 and C2 H6 are decreased with broader apertures in unit volume of K-illite slits. C2 H6 molecule is easier to full in K-illite slits and alkanes absorb on the site of Al-O-Si bond bridge in K-illite. The adsorption selectivity of C2 H6 /CH4 is more than unity. The content of CH4 suppresses the first and second adsorption peak of C2 H6 . This work can give some understandings about single and binary gas adsorption behavior in K-illite shales.